Pengaruh Pertumbuhan Penjualan, Efisiensi Operasional, dan Ukuran Perusahaan terhadap Pertumbuhan Laba: Studi Pada Perusahaan Teknologi di BEI - Ardian Koswantoro; Isyfa Fuhrotun Nadhifah (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Profit growth is an important indicator for evaluating corporate financial performance, particularly in the technology sector, which has experienced significant business dynamics following the pandemic and the emergence of the tech winter phenomenon. Fluctuations in the earnings of technology companies listed on the Indonesia Stock Exchange (IDX) indicate that increased sales do not necessarily translate into higher profitability, highlighting the need to examine factors influencing profit growth. This research investigates the effects of sales growth, operational efficiency, and firm size on profit growth among technology companies listed on the IDX during the 2022–2024 period. A quantitative approach was employed using secondary data derived from corporate financial statements. Samples were selected through a purposive sampling technique, resulting in 14 companies with a total of 42 observations. Data were analyzed using multiple linear regression. The findings reveal that sales growth and operational efficiency do not have a significant effect on profit growth. In contrast, firm size has a positive and significant influence on profit growth. These results suggest that technology firms with larger asset bases possess greater capacity to maintain financial stability and generate earnings growth than firms relying primarily on increased sales or operational cost efficiency. The study contributes to the literature on profit growth determinants in the Indonesian technology sector and provides practical implications for managers and investors in formulating strategic decisions.